PENGARUH PEMASARAN RELASIONAL DAN NILAI PELANGGAN TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN SEBAGAI VARIABEL MODERASI - Fitriana Puspitasari, Marjam Desma Rahadhini & Sumarno Dwi Saputra (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2017)
The purpose of this study was to analyze the effect of relationship marketing,customer value and customer satisfaction to customer loyalty and analyze the effect ofrelationship marketing and customer value on customer loyalty with satisfaction as amoderating variable. This study is a survey. The type of data used quantitative andqualitative data. The data source used primary data sources and secondary data. Thestudy population is consumer Warung Pecel Solo. The research sample of 100 peoplewith purposive sampling technique. The technique of collecting data used interviews,questionnaires and observations. Data were analyzed used multiple linear regressionand test of absolute difference. The results showed that relationship marketing has asignificant effect on customer loyalty. Value customers has a significant effect oncustomer loyalty. Satisfaction has a significant effect on customer loyalty. Satisfactiondoes not moderate the effect of relationship marketing on customer loyalty. Satisfactiondoes not moderate the influence of customer value on customer loyaltyKeywords: relationship marketing, customer value, satisfaction, loyalty